Recent development in occupational health services in Malaysia - Masilamani, R. (2010)
Globalizations and incorporating new technologies, innovations in industrial processes have brought in greater occupational health and safety challenges. In Malaysia, the Factory and Machinery Act 1967 set the stage for addressing the preliminary issues that arose due to early industrialization in Malaysia in the 1970s. The enactment of the Occupational Safety and Health Act 1994 set requirements to be met through promotion of occupational health and safety based on self regulation, complying with industrial codes of practice in operations, implementing occupational health and safety management strategies and the ultimate inculcation of an occupational health and safety culture1.